Risk factors for critical care admission in acute pancreatitis - Al Ubaidi, Reem; AlQaseer, Asma; AlKooheji, Mariam; Alderazi, Amer (International Surgery Journal, 2020)
Background: Acute pancreatitis is one of the most common gastrointestinal causes of emergency hospital admissions. One in four patients will develop severe acute pancreatitis requiring critical care admission (CCA) frequently for a prolonged period leading to a considerable burden on health care resources. The main objective of this study was to analyse factors that may predict the need for CCA in patients diagnosed with acute pancreatitis. Methods: In this study, authors analyzed the health records of all patients (154 patients) admitted to Salmaniya Medical Complex (SMC) with the diagnosis of acute pancreatitis. Results: A total of 10 (6.5%) and 24 (15.6%) patients were admitted to the intensive care unit (ICU) and surgical high dependency unit (SHDU) respectively. There were no differences between different admission locations when it came to age, gender, comorbidities, frequency of attacks and number of computed tomography (CT) scans. After adjusting for all covariates in a multivariate binary logistic regression, the following factors were found to predict CCA: Nationality OR (95% CI): 7.64 (1.14-51.29), dyslipidaemia etiology OR (95% CI): 0.025 (0.001-0.755) and CT severity index - CTSI (95% CI): 1.463 (1.014-2.111). CCA was associated with higher length of stay (6 days vs. 9 day) OR (95% CI): 0.79 (0.015-0.413) and higher in-hospital mortality (1.7% versus 17.6%) OR (95% CI): 5.58 (3.38-7.78). Conclusions: This study results indicate that nationality, dyslipidaemia etiology and CTSI were associated with higher CCA. ICU admission was associated with longer length of hospital stay and higher mortality rates.